Implementasi Model Pembelajaran Blended Learning pada Pelajaran PAI Kelas 7 di SMP PGRI 7 Kota Bandung - Rahman, Fadliany Aulia; Latipah, Siti; Hafipudin, Hafipudin; Nulhakim, Ihsan; Sutiawati, Siti (Permata : Jurnal Pendidikan Agama Islam, 2023)
This study aims to analyze the application of blended learning model in Islamic religious education class 7 at SMP PGRI 7 Bandung City. The research method used is a qualitative approach with a field research approach. The results showed that Islamic religious education teachers at SMP PGRI 7 Bandung City applied a blended learning model in Islamic religious education lessons in grade 7 as a learning solution after the Covid-19 pandemic. This model combines online and offline learning, which is varied with appropriate learning strategies and methods. The implementation of this learning model provides flexibility for students to learn independently, increases interaction between students and teachers, and expands access to learning resources. However, this learning model also has some disadvantages, such as the lack of student engagement during online learning and the gap in access to technology. Nevertheless, the implementation of blended learning model can be an effective solution to improve the quality of Islamic religious education learning at junior high school level.Keyword: Learning Model; Blended Learning; Islamic Education Lessons.